Initial report of prospective study of regional cooperation for imaging-based follow-up after curative renal cell carcinoma surgery - Ryo Tsukamoto; Tomokazu Sazuka; Hiroaki Sato; Takayuki Arai; Manato Kanesaka; Keisuke Ando; Yasutaka Yamada; Yusuke Goto; Yusuke Imamura; Shinichi Sakamoto; Junryo Rii; Hiroaki Kuramochi; et al. (Scientific Reports)
Abstract Late recurrence of renal cell carcinoma (RCC) is observed in some postoperative patients. In addition, some of these patients do not continue postoperative follow-up. Improving the regular follow-up process for the increased convenience of patients is expected. This aimed to assess the follow-up of patients after surgery for RCC. We initiated the relationship between Chiba University Hospital and Clinics project, which is ongoing. In this prospective, observational study, postoperative patients were asked to attend follow-ups in urology clinics. Imaging was performed at nearby imaging clinics. A total of 404 patients with RCC who underwent radical and/or partial nephrectomy were included in this analysis. A total of 283 patients continued follow-up at university hospitals and 121 patients were followed up in clinics. The median follow-up was 12.4 months. Patients with a long postoperative observation period tended to request continued follow-up at a university hospital. Patients living in municipalities with affiliated clinics were more likely to request follow-up at these clinics. The total loss to follow-up rate was lower than previous data showed. Comprehensive QOL and serum creatinine concentrations were not decreased in clinic group. This is the first study successfully collaborated with clinics in follow-up observation after RCC surgery.